Superparamagnetic Nanocrystals Clustered Using Poly(ethylene glycol)-Crosslinked Amphiphilic Copolymers for the Diagnosis of Liver Cancer - Ling Jiang; Jiaying Chi; Jiahui Wang; Shaobin Fang; Tingting Peng; Guilan Quan; Daojun Liu; Zhongjie Huang; Chao Lu (MDPI AG, 2023)
Superparamagnetic iron oxide (SPIO) nanocrystals have been extensively studied as theranostic nanoparticles to increase transverse (T2) relaxivity and enhance contrast in magnetic resonance imaging (MRI). To improve the blood circulation time and enhance the diagnostic sensitivity of MRI contrast agents, we developed an amphiphilic copolymer, PCPZL, to effectively encapsulate SPIO nanocrystals. PCPZL was synthesized by crosslinking a polyethylene glycol (PEG)-based homobifunctional linker with a hydrophobic star-like poly(ε-benzyloxycarbonyl-L-lysine) segment. Consequently, it could self-assemble into shell-crosslinked micelles with enhanced colloidal stability in bloodstream circulation. Notably, PCPZL could effectively load SPIO nanocrystals with a high loading capacity of 66.0 ± 0.9%, forming SPIO nanoclusters with a diameter of approximately 100 nm, a high cluster density, and an impressive T2 relaxivity value 5.5 times higher than that of Resovist®. In vivo MRI measurements highlighted the rapid accumulation and contrast effects of SPIO-loaded PCPZL micelles in the livers of both healthy mice and nude mice with an orthotopic hepatocellular carcinoma tumor model. Moreover, the magnetic micelles remarkably enhanced the relative MRI signal difference between the tumor and normal liver tissues. Overall, our findings demonstrate that PCPZL significantly improves the stability and magnetic properties of SPIO nanocrystals, making SPIO-loaded PCPZL micelles promising MRI contrast agents for diagnosing liver diseases and cancers.